Prognostic Value of the Geriatric Nutritional Risk Index in Non-Small Cell Lung Cancer Patients: A Systematic Review and Meta-Analysis - Wang, Haoyu; Li, Cui; Yang, Ruiyuan; Jin, Jing; Liu, Dan; Li, Weimin (Frontiers in Oncology, 2022)
Background: Novel evidences showed that the geriatric nutritional risk index (GNRI) may lead to poor prognosis of human cancers. Therefore, we conducted a meta-analysis to explore the impact of GNRI in lung cancer and the prognostic value of it. Methods: We searched the databases of PubMed, Web of science, Embase, Scopus, and Cochrane Library up to July, 2021 for relevant researches and merged the hazard ratios (HRs) and 95% confidence intervals (CIs) to evaluate the association between GNRI and overall survival (OS), cancer-specific survival (CSS), and recurrence-free survival (RFS) in patients with lung cancer. Results: Eight studies involving 2399 patients were included in our primary meta-analysis. The results indicated that lower level of GNRI was associated with poorer OS, RFS, and CSS of lung cancer patients (OS: HR=1.99, 95%CI: 1.68-2.35, p<0.0001) (RFS: HR=2.34, 95%CI: 1.11-4.95, p=0.0258) (CSS: HR=2.45, 95%CI: 1.43-4.18, p=0.0011). The association was robust after subgroup analysis and sensitivity analysis. Conclusions: GNRI may be a prognostic factor of lung cancer, which can lead to poorer survival. However, more prospective studies were necessary to confirm the results.